Четыре новых вида клещей-фитосейид фауны СССР (Parasitiformes, Phytoseiidae) - Колодочка, Л.А. (Вестник зоологии, 1979)
Four new species Amblyseius (Euseius) ucrainicus sp. n., A. (E.) kirghisicus sp. n., Anthoseius (Amblydromellus) salviae sp. n. and A. (Am.) aktherecus sp. n. from the Ukrainian and Kirghiz plants are described. Some ecological notes are given.